Risk-taking and the three institutional pillars - Malik, Sumeet (IE University, 2021)
This dissertation systematically looks at the interaction of risk-taking market actors with the three institutional pillars – regulative, normative, and socio-cognitive (Scott, 2013). Since institutions can define both market and non-market outcomes, each chapter of the thesis asks a question related to an institutional pillar. The first chapter asks how investors interpret and react to entrepreneurial orientation rhetoric in strictly regulated contexts. The second chapter asks, can business leaders act opportunistically at the cost of other stakeholders in their response to regulations? The final chapter asks, how can creative entrepreneurs balance the paradox of conforming to institutional pressures and offering novelty? The thesis contributes to management literature in several ways. First, it explains how investors perceive entrepreneurial orientation (EO) rhetoric in a highly regulated environment. Second, it provides evidence of CEOs exploiting the attention of markets to act opportunistically against stakeholders to preserve their personal wealth. Finally, it attempts to unravel the paradox of novelty and conformity for creative entrepreneurs driven by Schumpeterian rents.
La asunción de riesgos y los tres pilares institucionales.
Esta tesis examina sistemáticamente la interacción de los agentes del mercado que asumen riesgos con los tres pilares institucionales: el regulador, el normativo y el socio-cognitivo (Scott, 2013). Dado que las instituciones pueden definir resultados tanto de mercado como de no mercado, cada capítulo de la tesis plantea una pregunta relacionada con un pilar institucional. El primer capítulo se pregunta ¿cómo los inversores interpretan y reaccionan a la retórica de la orientación empresarial en contextos estrictamente regulados? El segundo capítulo se pregunta: ¿pueden los líderes empresariales actuar de forma oportunista a costa de otras partes interesadas en su respuesta a la normativa? El último capítulo se pregunta ¿cómo pueden los empresarios creativos equilibrar la paradoja de ajustarse a las presiones institucionales y ofrecer novedad? La tesis contribuye a la literatura de gestión de varias maneras. En primer lugar, explica cómo los inversores perciben la retórica de la orientación empresarial (OE) en un entorno altamente regulado. En segundo lugar, aporta pruebas de que los consejeros delegados aprovechan la atención de los mercados para actuar de forma oportunista contra las partes interesadas para preservar su riqueza personal. Por último, intenta desentrañar la paradoja de la novedad y la conformidad de los empresarios creativos impulsados por las rentas Schumpeterianas.
Keywords: Industrial studies; Market study; Ethics; Estudio de Mercado; Regulación Gubernamental del Sector Privado; Investigación Operativa; Procesos Cognitivos